Femmes et pornographes ? - Stéphanie Kunert (Genre, Sexualité et Société)
For this first issue of the revue, we interviewed four film-makers whose cinematographic art deconstructs the means and significations of pornography, representations of gender and sexuality.Emilie Jouvet, Maria Beatty, Catherine Corringer and Shue Lee Cheang express, in this interview, their vision of pornography, art and feminism.Wether their art is reclaimed as erotic, explicit or pornographic, they have in common a creative and somewhat “queer” approach of sexual representations.